Nuclear phenotypes and morphometry of human secretory prostate cells: A comparative study of benign and malignant lesions in Brazilian patients - Taboga, Sebastião R.; Santos, Adriana B. dos [UNESP]; Gonzatti, Adriana G. R.; Vidal, Benedicto C.; Mello, Maria Luiza S. (Firenze University Press, 2003)
Prostatic lesions in Brazilian patients with benign prostatic hyperplasia (BPH, 26 cases) or adenocarcinoma (AC, 25 cases) were compared by qualitative microscopy and morphometric analysis. In 12 cases of BPH, prostate regions with no histological alterations were considered as controls (Ct). Archival material consisted of formalin-fixed, paraffin-embedded specimens obtained from prostatic transurethral resection and radical prostatectomy. Haematoxylin/eosin (HE)-stained sections were used to estimate the nuclear areas, perimeters and form factor values. HE-stained sections from AC specimens were also used for Gleason grading. BPH, AC and Ct could be discriminated by their nuclear areas and nuclear perimeters, but not by the nuclear form factor parameter. No significant differences were found when the AC data were compared using the combined version or the predominant grade version of the Gleason score (p = 0.8380 for nuclear area; p = 0.6076 for nuclear perimeter; p = 0.9202 for nuclear form factor; n = 200 nuclei per patient). This finding indicates that there is extensive heterogeneity in the size and shape of the nucleus in AC cells. These results also show that although the nuclear morphometry served to discriminate BPH and AC from each other and from Ct, it was not sufficient to correlate AC lesions with their respective Gleason scores in the human population analyzed.
Keywords: Benign lesions; Brazilian patients; Human prostate; Malignant lesions; Nuclear morphometry